2022
DOI: 10.1590/fst.61020
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Rheological, & Sensory Characteristics of Yogurt Fortified with Ball-Milled Roasted Chickpea Powder (Cicer arietinum L.)

Abstract: This study was aimed at evaluation of effects of ball-milled roasted chickpea (RC) powder on physicochemical, rheological and sensorial properties of yogurt supplemented with RC levels of 1 (RCY1), 2 (RCY2), 3 (RCY3), 4 (RCY4), and 5 g/100 mL (RCY5). Results showed a gradual decline in the pH of pre-inoculated samples with corresponding increases in powder concentration from 1 to 5 g/ 100 mL. Degrees of lightness and yellowness increased in supplemented samples as compared to control (RCY0). Higher firmness wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In this regard, lower temperature allows to take longer time for setting of curd whereas gradually increasing tendency in temperature causes increased syneresis in yogurt (Arab et al, 2022 ). Moreover, it has already been suggested in the published literature that dietary fiber of plant origin has absorptive role regarding absorption of serum or whey release from yogurt gel structure (Raza et al, 2021 ). The increasing WHC trend of yogurt with an increase in the concentration of powder might be due to an increase in TSS resulted because of the addition of WMFP.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, lower temperature allows to take longer time for setting of curd whereas gradually increasing tendency in temperature causes increased syneresis in yogurt (Arab et al, 2022 ). Moreover, it has already been suggested in the published literature that dietary fiber of plant origin has absorptive role regarding absorption of serum or whey release from yogurt gel structure (Raza et al, 2021 ). The increasing WHC trend of yogurt with an increase in the concentration of powder might be due to an increase in TSS resulted because of the addition of WMFP.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rinaldoni et al (2012), fermented beverages such as yogurt must present minimum total solids of 12 g•100 g -1 in order to obtain products with adequate viscosity and texture. The higher values of protein and dry material in FB represent an important role in the technological properties of the product, as these parameters are determinants to obtain desirable rheological properties in fermented beverages (Rinaldoni et al, 2012;Raza et al, 2022;Oliveira et al, 2009). The higher values of dry matter and protein in FB can be explained either by the addition of inulin or by the higher protein content in WSSE when compared to the caprine Table 1.…”
Section: Fermented Beveragesmentioning
confidence: 99%
“…thermophillus and Lactobacillus delbrueckii subsp. bulgaricus (Raza et al, 2022). Many studies have pointed out that the benefits of yogurt consumption are attached to the viability of these lactic acid bacteria (Hadjimbei et al, 2020), where, according to the Brazilian regulation, the minimum required is 10 6 CFU•g -1 (Brasil, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polysaccharides found in OF tend to be absorbed onto the protein surface and thus can act as bridges between proteins, resulting in the formation of a strong gel structure that provides higher elastic characteristics (Hamet et al, 2015). Similarly, Raza et al (2022) reported that the addition of roasted chickpea powder improved the rheological characteristics of yogurts and led to improved structural configurations. In addition, the application of HPH caused an increase in the G′ value.…”
Section: Dynamic Shear Propertiesmentioning
confidence: 99%